Assessment of rational use of fixed dose combinations in hypertension in a tertiary care teaching hospital in north India - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Advances in Medicine, 2018)
Background: Fixed-dose combination (FDC) agents could be considered as an effective therapy in chronic illnesses like hypertension, which have multifactorial etiology. At present, many FDCs have come into the market without being assessed for their efficacy, safety and rationality by the drug regulatory authorities. The objective of the present study was to assess the rational use of fixed dose drug combinations in hypertension. Methods: It was a cross-sectional observational study conducted in the cardiology outpatient department of ASCOMS and H, Sidhra, Jammu, Jammu and Kashmir from February 2016 to July 2016. In the study 92 prescriptions of hypertensive patients who were on anti-hypertensive fixed-dose drug combinations (FDCs) were recruited after thoroughly evaluated for inclusion and exclusion criteria. Data obtained includes the demographic profile of the patients, pattern of the prescribed FDCs in hypertension, evaluation of the rationality of the FDCs based upon the comprehensive seven-point criteria developed by Panda et al. Results: In the present study, about sixteen different anti-hypertensive FDCs were observed in the prescriptions of 92 patients during six-month period. It was observed that about 93.75% of FDCs were dual drug combinations. Among the dual drug combinations, most commonly used combination was Olmesartan (ARB; Angiotensin receptor blocker) + Amlodipinine (Calcium channel blocker) in 17.4% of patients. It was also observed that among the 16 different anti-hypertensive fixed dose combinations analysed, 12 FDCs (75%) were found to be rational and 4 FDCs (25%) were found to be irrational. Conclusions: In the present study it was found that 75% of the FDCs prescribed were rational and 25% were irrational. Therefore, before marketing the FDCs proper assessment of their efficacy, safety and rationality should be done.